New classification of periodontal diseases and periimplant conditions (2017) - Борисенко, Анатолій Васильович (Actual Dentistry, 2019)
Urgency. A classification scheme for periodontal diseases and conditions is necessary for clinicians to properly diagnose and treat patients as well as for scientists to investigate etiology, pathogenesis, natural history, and treatment of the diseases and conditions. This paper summarizes the proceedings of the World Workshop on the Classification of Periodontal Diseases and Conditions. This introductory paper presents an overview for the new classification of periodontal diseases and conditions, along with a condensed scheme for each of four workgroup sections. Changes to the 1999 classification are highlighted and discussed. The possibility of adaptation of this classification of periodontal diseases to the conditions of Ukraine is shown. Key words: periodontal diseases, classification